Tuberculosis surveillance in Spain (2015-2021) (Boletín Epidemiológico Semanal, 2023)
Introduction: Tuberculosis (TB) is a notifiable disease in Spain. The objective of this study was to analyze its epidemiological situation during the period 2015-2021.Method: Descriptive epidemiological analysis of TB cases reported by the CCAA to the National Epidemiological Surveillance (RENAVE) during 2015-2021. The analyzed variables included sex, age, CCAA, year of reporting, country of birth and residence, location, date of symptom onset and treatment initiation, treatment outcome, HIV status and diagnosis information. A descriptive analysis of the main variables and a temporo-spacial analysis of the notification rates were carried out.Results: In 2021, 3,754 cases of TB were reported in Spain, with a notification rate of 7.61 per 100,000 population. This represented a 2.18% decrease compared to 2020 and a 28.07% decrease compared to 2015. Throughout the study period, a higher number of cases were observed in males (ratio 1.6-1.7), and there was a decreasing trend in notification rates in all CCAA, except Ceuta. This decline in rates was more pronounced for pulmonary forms. The case fatality remained stable during the study period. The quality of the provided information improved between 2015 and 2021 for some variables, but remained essential variables such as “treatment outcome” or HIV diagnosis.Conclusions: The incidence of TB in Spain decreased from 2015 to 2021, particularly for pulmonary forms. Two of the WHO’s targets for 2020 were achieved, but the 2035 target appears unlikely. Significant deficiencies in the quality of information persist.
Keywords: Tuberculosis; surveillance; Spain; RENAVE.